Utilitarianism Perspective on The Use of E-Stamps in Business Practices in Indonesia - Abbas, Ilham; Putra, Aditya Halim Perdana Kusuma (Magister of Law, Faculty of Law, University of Mataram, 2024)
The implementation of e-stamps in Indonesia as a replacement for conventional stamps has the potential to increase efficiency and effectiveness in administrative and business processes, but also raises ethical challenges related to data security, technology accessibility, and fairness in its implementation, which need to be evaluated from a utilitarian perspective to ensure the greatest benefit to the wider community. The purpose of this study is to analyze the implementation of e-stamps in business practices in Indonesia from a utilitarian perspective, by evaluating the increased efficiency and benefits for business actors and comparing the overall impact on society with the conventional stamp system. This study uses a normative legal research method with a legislative and conceptual approach, analyzing primary, secondary, and tertiary legal materials through literature studies, and applying descriptive-analytical qualitative analysis to examine the utilitarian perspective in the use of e-stamps in business practices in Indonesia. The results of the study indicate that the use of e-stamps in business practices in Indonesia, viewed from a utilitarian perspective, provides greater benefits to society as a whole compared to the conventional stamp system. E-stamps increase efficiency, transparency, and legal certainty, as well as reduce administrative costs, which are beneficial to various parties including large business actors, SMEs, and the government. Despite challenges such as limited digital infrastructure in some areas, the benefits of e-stamps are considered significant in driving productivity, economic welfare, and creating a more conducive business environment. With the support of a clear legal framework, e-stamps have the potential to become an efficient and beneficial instrument for all levels of Indonesian society, driving economic inclusion and more sustainable growth..